Do Sebacinales commonly associate with plant roots as endophytes ? - Selosse, Marc-André; Dubois, Marie-Pierre; Alvarez, Nadir (My University, 2009)
Sebacinales are basal Hymenomycetes with diverse mycorrhizal abilities, ranging from ectomycorrhizae to ericoid and orchid mycorrhizae. Several previous PCR or isolation works raised the possibility that Sebacinales are endophytes in plant roots. We tested this hypothesis in an isolation-independent approach by using specific PCR primers for ribosomal DNA of Sebacinales on AM mycorrhizal or non-mycorrhizal roots. Thirty-nine plant species were sampled on a Caribbean and two European sites (3 repetition per species and site), covering 25 families in monocots and eudicots. PCR signals were obtained from 40 samples (28.9 %) from 27 species (69.2 %) and all sites. Whenever sequencing was successful, a sequence belonging to Sebacinales was recovered. A phylogenetic approach revealed that 13 of them belonged to clade B (encompassing ericoid and orchid mycorrhizal species) and 4 to clade A (usually encompassing only ectomycorrhizal species). These data suggest that Sebacinales may be endophytic in many angiosperm roots, and that this condition is plesiomorphic in Sebacinales. They bridge the gap between physiological studies, inoculating Sebacinales (Piriformospora indica or Sebacina vermifera) on diverse plants and molecular ecology, hitherto restricting Sebacinales to mycorrhizal interactions. Structural and functional aspects of the interaction deserve further studies.
Keywords: Endophytes; Piriformospora indica; Root fungi; Sebacinales; Tropical fungi